Modelling solute transport and deformation of clay soil under the chemo-hydro-mechanical coupling actions based on fractal theory - Zheng, Xinjiang; Chen, Xianyuan; Chen, Zhibo; Zhu, Mengyuan; Li, Xiaoyue (Scientific reports, 2025)
The interactions between chemical, hydraulic, and mechanical processes in clay soils has garnered significant attention in various fields. It is important to study the transport of chemical substances and the deformation of the clay layer under the combined action of chemical solution and mechanical loading. Clay is a typical porous medium, primarily composed of soil skeleton and pores, with the shape, size, and distribution of clay pores being random, making it difficult to accurately describe using traditional geometry. A fractal model can be used to simulate clay soils. This study leverages the fractal theory of clay, incorporating the generalized effective stress principle in chemical solutions and a fractal model for the diffusion of chemical substances. A chemo-hydro-mechanical coupling model based on fractal theory is developed. Simulation results show that an increase in fractal dimension corresponds to a heightened roughness of the pore surfaces and an increased tortuosity of the pore channels, which significantly amplify the resistance to solute diffusion, thereby retarding the rate of solute transport. As a result, the magnitude of the maximum negative pore pressure within the clay layer, leading to a longer time required for complete pore pressure dissipation. Additionally, the deformation of the clay layer is larger.